Providing a Framework Based on Decision-Making Methods To Assess Safety Risk in Construction Projects - Chen, Tzu-Chia; Zahar, Marziah; Voronkova, Olga Yuryevna; Khoruzhy, Valery Ivanovich; Morozov, Ivan Vladimirovich; Javad Esfahani, Mohammad (International Journal of Industrial Engineering and Management, 2022)
The risk management process is a systematic and logical process that should include identification, analysis, measurement, and dealing with risk-taking into account the facilities, conditions, and context of the organization. Today, work-related accidents, as one of the important factors in losing efficient manpower and Waste of capital and time, are considered a threat to the development and progress of any country. Therefore, failure to pay attention and assess the safety risk in the construction industry will cause irreparable problems and impose high costs on the project. Work-related accidents are not entirely accidental, so the most effective measures can be taken to control and reduce them while anticipating. Appropriate hi-tech in the analysis of hazards in industries is an important step in determining effective measures to reduce accidents. This study aims to use the most appropriate techniques available to identify hazards and assess the risk in order to improve safety, reduce accidents and costs and save time. In this research, to identify, evaluate and rank the safety risks of construction projects with fuzzy approach and TOPSIS method, which we have dealt with according to the importance of each risk, appropriate strategies and response programs should be applied according to them. The main finding of this research is that Excavation is the most important risky work in construction projects that needs more attention to reduce total risks. Article history: Received (Nay 25, 2021); Revised (July 21, 2021); Accepted (August 05, 2021); Published online (December 09, 2021)